A novel optical radio on fiber multi-channel by micro ring resonator system - Pornsuwancharoen, N.; Boonmeewised, K.; Kitcharoen, N.; Sansoda, B.; Yupapin, P. P.; Phromloungsri, R. (My University, 2012)
We propose a novel system that can be used to generate the new optical radio on fiber communication continuous variable channel using a Gaussian pulse propagating within a nonlinear micro-nanoring resonator system. By using the wide range of the Gaussian input for instance, when the input pulses of the common lasers with centre wavelengths from 1,300 nm are used, which this system is simple for used. Results obtained have shown that more available wavelength bands and frequency domain(THz) from the different ring parameter and wavelengths can be generated, which can be used to form new optical to high frequency ranges, whereas the use of the very high channel capacity for personal wavelength and very high security and multi-channel in network applications is plausible. © 2010 Published by Elsevier Ltd.
Keywords: High frequency; RoF and multi channel; Wireless security